Growth Characteristics of Female Radiation/Clinical Oncologists in South Asia: Assessment of Gender Neutrality and Leadership Position. Issue 10 (October 2022) - Sarkar, B.; Munshi, A.; Ganesh, T.; Manikandan, A.; Bhattacharjee, B.; Pun, R.; Imbulgoda, N.; Yasmin, T.; Pradhan, A.
Abstract: Aim: To evaluate the temporal growth pattern of female radiation/clinical oncologists (FRCOs) and, if applicable, predict the gender neutrality in different countries of South Asia. Materials and methods: South Asia is composed of Afghanistan, Bhutan, Maldives, Bangladesh, India, Nepal, Pakistan and Sri Lanka. The growth pattern of FRCOs in the latter five countries having radiation oncology facilities was evaluated from respective national registration data. Based on the average annual differential growth rate, together with the already existing female and male radiation/clinical oncologists (MRCOs), the cumulative numbers of FRCOs and MRCOs were forecasted for the next 10 years. The data regarding FRCOs in a leadership position were also calculated from different sources. Results: The total number of radiation/clinical oncologists in the region was 4074, of which 91.8% were in India, because of its vast population. The overall number of FRCOs and MRCOs stood at 1370 and 2704, with a 1:2 female:male ratio. The average incremental annual growth of FRCOs in India was the highest (12.7 persons/year) and Nepal was the lowest (0.4 persons/year), with no data from Pakistan. If the current growth rate is sustained, Indian gender neutrality will be achieved by 2027–2030. In other countries, gender neutrality is unlikely to be achieved in the near future. With regards to leadership positions, 56–77 radiation oncology departments in India, one each in Bangladesh and Sri Lanka are headed by FRCOs, whereas Nepal and Pakistan have none. Conclusions: With the current growth rate of FRCOs and MRCOs, India will achieve gender parity within a decade; however, the rest of the countries will not achieve this in the near future. Analysis of radiation/clinical oncologists' registration data with their respective national bodies revealed an encouraging growth in the number of FRCOs as against their male counterparts in the last 5 years, compared with previous decades, especially in Bangladesh, Sri Lanka and India. Sri Lanka show high gender neutrality and adopted a multi-tasking and holistic approach of clinical oncology practices as also seen in Scandinavian countries. Such practice may be helpful to improve gender equality in radiation/clinical oncology practice for the other countries in the South Asian region. Highlights: An analysis of the woman participants in radiation and clinical oncology. Analyse the growth characteristics of woman radiation oncologist in south Asia. Identifies the woman in leadership position (radiation/clinical) oncology. Include India, Bangladesh, Pakistan, Nepal and Sri Lanka. Predict the gender neutrality in radiation/clinical oncology for next decade.